Protocol for real-time assessment of energy metabolism in dissociated mouse retinal photoreceptors using a SeahorseXFe24 analyzer - Maria Yera; Joshua J. Wang; Sarah X. Zhang (STAR Protocols)
Summary: Defects in retinal metabolism have been linked to the onset and progression of various retinal diseases. Herein, we provide a protocol for measuring bioenergetics in dissociated mouse retinal photoreceptors. We outline detailed instructions for obtaining morphologically intact and viable photoreceptor cells from adult mice and preparing the cells for metabolic analysis using a SeahorseXFe24 analyzer. This protocol allows a real-time assessment of mitochondrial respiration and glycolysis in retinal photoreceptors in response to genetic modifications or pathological insults in mouse models. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.